Bufalin induces apoptosis in vitro and has Antitumor activity against human lung cancer xenografts in vivo. Issue 4 (22nd July 2016) - Wu, Shin‐Hwar; Bau, Da‐Tian; Hsiao, Yung‐Ting; Lu, Kung‐Wen; Hsia, Te‐Chun; Lien, Jin‐Cherng; Ko, Yang‐Ching; Hsu, Wu‐Huei; Yang, Su‐Tso; Huang, Yi‐Ping; Chung, Jing‐Gung
ABSTRACT: Bufalin has been shown to be effective against a variety of cancer cells, but its role in lung cancer has never been studied in an animal model. In this study, we evaluated bufalin effects in a human lung cancer cell line NCI‐H460 both in vitro and in vivo . Bufalin caused significant cytotoxicity in NCI‐H460 cells at a concentration as low as 1 μM. DNA condensation was observed in bufalin‐treated cells in a dose‐dependent manner. Mitochondrial membrane potential (ΔΨm ) was reduced and reactive oxygen species (ROS) were increased in bufalin‐treated NCI‐H460 cells. Levels of several proapoptotic proteins such as Fas, Fas‐ligand, cytochrome c, apoptosis protease activating factor‐1, endonuclease G, caspase‐3 and caspase‐9 were increased after bufalin treatment. At the same time, anti‐apoptotic B‐cell lymphoma 2 protein levels were reduced. Bufalin decreased glucose regulated protein‐78 gene expression but increased growth arrest‐ and DNA damage‐inducible 153 gene expression. Bufalin injected intraperitoneally in a dose‐dependent manner reduced tumor size in BALB/C nu/nu mice implanted with NCI‐H460 cells. Bufalin injection did not produce significant drug‐related toxicity in experimental animals except at a high dose (0.4 mg kg −1 ). In conclusion, low concentrations of bufalin can induce apoptosis in the human lung cancer cell line NCI‐H460 in vitro . Bufalin also reduced tumor size in mice injected with NCI‐H460 cells without significant drug‐related toxicity. These results indicate that bufalin may have potential to be developed as an agent for treating human non‐small cell lung cancer. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1305–1317, 2017.